Dispersion composition
Patent Information
- Application Number
- JP2024007217
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-01-22
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2044-01-22
AI Technical Summary
【0010】 本発明によれば、優れた付着性(接着性、密着性)を示すことができ、プラスチック基材等の基材上に塗布した場合に、耐温水性、高圧洗車性を有する塗膜を形成できる、分散体組成物を提供できる。
Smart Images

Figure 0007636594000001 
Figure 0007636594000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a dispersion composition, and more particularly to a dispersion composition containing an acid-modified chlorinated polyolefin, which is capable of exhibiting good high-pressure car washability and water-resistant adhesion in warm water. [Background technology]
[0002] From the viewpoint of reducing the environmental load and manufacturing costs, the material of the exterior panels of automobiles is being replaced from conventional steel sheets to plastic substrates. The coating film formed on the plastic exterior panels is required to have the same coating performance as that of the coating film formed on the steel exterior panels.
[0003] On the other hand, plastic substrates are generally non-polar substrates, have low surface free energy, and paint is difficult to adhere to, especially when the plastic substrate has crystallinity. In addition, one of the performance requirements for coatings on exterior parts of automobiles is high water resistance. For reasons such as the need to respond to accelerated tests for evaluating high-pressure car washability and the need to respond to temperature changes in each season, coatings are required to be highly resistant not only to water at room temperature, but also to hot water.
[0004] For example, Patent Document 1 describes that in an aqueous dispersion containing a modified polyolefin modified with a (meth)acrylic acid ester, when the glass transition temperature of the homopolymer of the (meth)acrylic acid ester is 50 to 90°C and the hydroxyl value X is 17 mgKOH / g or more and 50 mgKOH / g or less, the aqueous dispersion can exhibit good adhesion and resistance to warm water and can be used as a paint or binder for plastic substrates of automobiles. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2020-26487 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, coating films obtained using aqueous dispersions of resins modified with conventional (meth)acrylic acid esters, such as those described in Patent Document 1, may not exhibit the high level of adhesion and coating film properties required for coating films on exterior panels, and in particular may have insufficient high-pressure car washability.
[0007] An object of the present invention is to provide an aqueous dispersion composition which, even when applied to a plastic substrate, can exhibit good adhesion to the substrate and can form a coating film which exhibits coating film properties such as high-pressure car washability and warm water resistance. [Means for solving the problem]
[0008] In order to solve the above problems, the present inventors have conducted extensive research and have found that a coating film having good adhesion and coating film properties such as warm water resistance and high-pressure car washability can be formed by using a composition containing an acid-modified chlorinated polyolefin resin having predetermined physical properties in the form of a dispersion, and have thus completed the present invention.
[0009] That is, the inventors provide the following. [1] Component A: an acid-modified chlorinated polyolefin having a degree of chlorination of 17 to 23% by weight and a glass transition temperature of 0 to 10°C; Component B: nonionic surfactant, Component C: a basic compound, and Component D: Aqueous medium Including, A dispersion composition, in which the content of component B is 10% by weight or more when component A is taken as 100% by weight. [2] The dispersion composition according to [1], wherein the acid-modified chlorinated polyolefin has a weight average molecular weight of 100,000 to 150,000. [3] The dispersion composition according to [1] or [2], wherein the acid-modified chlorinated polyolefin has a softening point of 70 to 100°C. [4] The dispersion composition according to any one of [1] to [3], wherein Component B contains a polyoxyethylene alkyl ether-based nonionic surfactant. [5] The dispersion composition according to any one of [1] to [4], wherein component C contains a primary amine. [6] Component E: The dispersion composition according to any one of the items [1] to [5], further comprising a glycol ether compound having a molecular weight of less than 200. [7] The dispersion composition according to any one of [1] to [6], which is a paint or a binder. Effect of the Invention
[0010] According to the present invention, it is possible to provide a dispersion composition which exhibits excellent adhesion (bonding property, adhesion) and which, when applied to a substrate such as a plastic substrate, can form a coating film which is resistant to warm water and high-pressure car washes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below based on preferred embodiments thereof.
[0012] [1. Composition] The composition contains components A to D, and preferably further contains component E.
[0013] [1.1 Component A: Acid-modified chlorinated polyolefin] Component A is an acid-modified chlorinated polyolefin. The acid-modified chlorinated polyolefin is a modified polyolefin obtained by subjecting a raw material polyolefin to modification treatment including acid modification and chlorination. In this specification, a modified polyolefin obtained by modification treatment including acid modification (whether or not chlorination is included) is called an acid-modified polyolefin, and a modified polyolefin obtained by modification treatment including chlorination (whether or not acid modification is included) is called a chlorinated polyolefin.
[0014] (Polyolefin (raw material)) The polyolefin raw material is not particularly limited, and may be a homopolymer of one type of olefin or a copolymer of two or more types of olefin. In addition, when it is a copolymer, it may be a random copolymer or a block copolymer. As the olefin, α-olefin is preferably used. Examples of α-olefin include ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, and 1-octene. From the viewpoint of exhibiting sufficient adhesion to non-polar resin substrates such as polypropylene substrates, the polyolefin is preferably polypropylene (propylene homopolymer), ethylene-propylene copolymer, propylene-1-butene copolymer, or ethylene-propylene-1-butene copolymer, and more preferably ethylene-propylene copolymer.
[0015] In this specification, polypropylene refers to a polymer whose base unit is a structural unit derived from propylene. Ethylene-propylene copolymer refers to a copolymer whose base unit is a structural unit derived from ethylene and a structural unit derived from propylene. Propylene-1-butene copolymer refers to a copolymer whose base unit is a structural unit derived from propylene and a structural unit derived from 1-butene. These polymers may contain a small amount of structural units derived from other olefins other than the above-mentioned base units. This content may be an amount that does not significantly impair the inherent performance of the resin. Such structural units derived from other olefins may be mixed in, for example, during the process leading up to the production of the modified polyolefin resin.
[0016] The polyolefin preferably contains 60 mol % or more of propylene-derived structural units out of 100 mol % of structural units. When the propylene-derived structural units are contained in the above range, adhesion to substrates or molded articles such as non-polar resins (e.g., propylene resins) can be ensured.
[0017] The ethylene-propylene copolymer and propylene-butene copolymer may be either a random copolymer or a block copolymer. These copolymers preferably contain 5 to 50 mol % of ethylene-derived structural units or butene-derived structural units, and 50 to 95 mol % of propylene-derived structural units, based on 100 mol % of structural units.
[0018] (Production method of polyolefin) Examples of methods for producing polyolefins include methods using polymerization catalysts such as Ziegler-Natta catalysts and metallocene catalysts, and methods using metallocene catalysts are preferred. Polyolefins obtained using metallocene catalysts usually have a narrow molecular weight distribution. In addition, when polyolefins are copolymers, they usually have excellent random copolymerizability, a narrow composition distribution, and a wide range of comonomers that can be copolymerized.
[0019] The metallocene catalyst may be a known one, and is preferably obtained by combining the following components (1) and (2), and, if necessary, (3). Component (1): a metallocene complex which is a transition metal compound of Groups 4 to 6 of the periodic table having at least one conjugated five-membered ring ligand; Component (2): Ion-exchange layered silicate; Ingredient (3): Organoaluminum compound.
[0020] (Polyolefin Melting Point) The melting point of the polyolefin is preferably 80°C or higher and 150°C or lower, and more preferably 85°C or higher and 140°C or lower.
[0021] (Weight average molecular weight of polyolefin) The weight average molecular weight of the polyolefin is not less than 70,000 and less than 500,000, and preferably not less than 80,000 and less than 400,000. In this specification, the weight average molecular weight (Mw) can be measured by GPC using polystyrene as a standard substance.
[0022] The polyolefin may be used alone or in combination of two or more kinds. In the case of a combination of two or more kinds, the weight ratio of each compound is not particularly limited.
[0023] (Acid modification (introduction of α,β-unsaturated carboxylic acid or its derivative)) The acid modification can be achieved by the introduction (graft modification) of an α,β-unsaturated carboxylic acid or a derivative thereof. Examples of α,β-unsaturated carboxylic acids and derivatives thereof include maleic acid, maleic anhydride, fumaric acid, citraconic acid, citraconic anhydride, mesaconic acid, itaconic acid, itaconic anhydride, aconitic acid, aconitic anhydride, himic anhydride, (meth)acrylic acid, (meth)acrylic acid esters, N-methyl(meth)acrylamide, hydroxyethyl(meth)acrylamide, (meth)acryloylmorpholine, and combinations of two or more selected from these. Among these, α,β-unsaturated carboxylic acid anhydrides and (meth)acrylic acid esters are preferred, and maleic anhydride is more preferred.
[0024] The α,β-unsaturated carboxylic acid and its derivative may be one or more, and may be a combination of one or more α,β-unsaturated carboxylic acids and one or more derivatives thereof, a combination of two or more α,β-unsaturated carboxylic acids, or a combination of two or more derivatives of α,β-unsaturated carboxylic acids. In the case of a combination of two or more types, the weight ratio of each is not particularly limited.
[0025] (Degree of acid modification (amount of α,β-unsaturated carboxylic acid and its derivatives introduced)) The degree of acid modification represents the amount (graft weight) of α,β-unsaturated carboxylic acid and its derivatives introduced. The degree of acid modification is preferably 0.1% by weight or more, more preferably 0.5% by weight or more, based on 100% by weight of unmodified polyolefin. By having a graft weight of 0.1% by weight or more, the adhesion of the dispersion composition to the substrate can be maintained. The upper limit is preferably 10% by weight or less, more preferably 8% by weight or less, and even more preferably 4% by weight or less. This makes it possible to prevent the generation of unreacted grafted material, and to obtain sufficient adhesion to the substrate. Therefore, the amount of α,β-unsaturated carboxylic acid and its derivatives introduced is preferably 0.1 to 10% by weight, more preferably 0.1 to 8% by weight, and even more preferably 0.5 to 4% by weight. The amount (graft weight) of α,β-unsaturated carboxylic acid or its derivatives introduced can be measured by alkali titration or Fourier transform infrared spectroscopy.
[0026] (Acid Denaturation Method) The acid modification is not particularly limited as long as it is a method capable of introducing α,β-unsaturated carboxylic acid or its derivative into polyolefin or chlorinated polyolefin (preferably polyolefin), and examples thereof include a melting method and a solution method. The melting method has the advantage that the operation is simple and the reaction can be carried out in a short time. The solution method can obtain a uniform graft polymer with few side reactions. The melting method is a method in which a raw material containing a polyolefin, an α,β-unsaturated carboxylic acid or its derivative is heated and melted in the presence of a radical polymerization initiator to react with an α,β-unsaturated carboxylic acid or its derivative. The temperature of the heat melting may be equal to or higher than the melting point, and is preferably equal to or higher than the melting point and 300°C or lower. When the heat melting is carried out, an apparatus such as a Banbury mixer, a kneader, or an extruder can be used. The solution method is a method in which a raw material containing a polyolefin α,β-unsaturated carboxylic acid or its derivative is dissolved in an organic solvent, and then heated and stirred in the presence of a radical polymerization initiator to cause a reaction. Examples of the organic solvent include aromatic solvents such as toluene and xylene. The reaction temperature is preferably 100 to 180°C. When two or more compounds which are α,β-unsaturated carboxylic acids and derivatives thereof are used, they may be added to the reaction system all at once or successively.
[0027] The radical reaction initiator may be, for example, a thermal polymerization initiator that generates free radicals when heated, and examples thereof include organic peroxide compounds and azonitriles. Examples of the organic peroxide compounds include di-tert-butyl peroxide, dicumyl peroxide, tert-butyl cumyl peroxide, dibenzoyl peroxide, benzoyl m-tolyl peroxide, di(m-tolyl)benzoyl, dilauryl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, cumene hydroperoxide, tert-butyl hydroperoxide, 1,1-bis(tert-butylperoxy)-3,5,5-trimethyl Examples of the azonitriles include cyclohexane, 1,1-bis(tert-butylperoxy)-cyclohexane, cyclohexanone peroxide, tert-butylperoxy-benzoate, tert-butylperoxyisobutyrate, tert-butylperoxy-3,5,5-trimethylhexanoate, tert-butylperoxy-2-ethylhexanoate, tert-butylperoxyisopropyl carbonate, tert-butylperoxyoctoate, and cumylperoxyoctoate. Examples of the azonitriles include 2,2-azobis(2-methylbutyronitrile), 2,2-azobisisobutyronitrile, 2,2-azobis(2,4-dimethylvaleronitrile), and 2,2-azobis(4-methoxy-2,4-dimethylvaleronitrile).
[0028] (Chlorination) The chlorination can be carried out by a method capable of introducing chlorine into polyolefin or acid-modified polyolefin (preferably into acid-modified polyolefin). When introducing chlorine, polyolefin or acid-modified polyolefin may be dissolved in a chlorine-based solvent such as chloroform in advance. The introduction of chlorine is usually carried out by blowing chlorine gas into the reaction system. The blowing of chlorine gas may be carried out under irradiation of ultraviolet light, or in the presence or absence of a radical reaction initiator. The pressure when blowing chlorine gas is not limited, and may be normal pressure or pressure. The temperature when blowing chlorine gas is not particularly limited, but is usually 50 to 140°C. Examples of the radical reaction initiator include those exemplified as radical polymerization initiators that can be used in acid modification. The amount of the radical reaction initiator used in chlorination is preferably 0.001% by weight to 1% by weight, more preferably 0.01% by weight to 0.1% by weight, based on 100% by weight of the raw material resin. After the introduction of chlorine, the chlorine-based solvent in the system is usually distilled off under reduced pressure or replaced with an organic solvent.
[0029] (Chlorination degree (amount of chlorine introduced)) The chlorination degree of the acid-modified chlorinated polyolefin represents the chlorine content (graft amount of chlorine) relative to the polyolefin (including the acid-modified polyolefin) before chlorination. The chlorination degree is 17% by weight or more, preferably 18% by weight or more, 19% by weight or more, or 20% by weight or more. The upper limit is 23% by weight or less, preferably 22% by weight or less. By having the chlorination degree in the above range, good adhesion to the substrate can be obtained. The chlorination degree can be measured based on JIS-K7229. That is, it can be measured using the "oxygen flask combustion method" in which the chlorinated polyolefin is burned in an oxygen atmosphere, the generated gaseous chlorine is absorbed with water, and the amount is quantified by titration. The chlorination degree can be adjusted, for example, by the type of polyolefin resin, the scale of the chlorination reaction, the reaction apparatus used for chlorination, the amount of chlorine gas blown in, and the time.
[0030] (Order of acid modification and chlorination) In the method for producing an acid-modified chlorinated polyolefin, the order of acid modification and chlorination is not particularly limited, and an acid-modified polyolefin may be chlorinated, or a chlorinated polyolefin may be acid-modified, with the former being preferred.
[0031] (Other modifications) The acid-modified chlorinated polyolefin may be modified by any known method other than acid modification or chlorination.
[0032] (Glass transition temperature of acid-modified chlorinated polyolefin) The glass transition temperature Tg of the acid-modified chlorinated polyolefin is 0°C or higher, preferably 1°C or higher, 2°C or higher, 3°C or higher, or 4°C or higher, and more preferably 5°C or higher. This improves the adhesion of the coating film to the substrate after immersion in hot water, and improves the hot water resistance of the coating film. The upper limit is 10°C or lower. This gives the coating film appropriate flexibility, and improves the adhesion of the coating film to the substrate. Therefore, Tg is 0 to 10°C, preferably 1 to 10°C, 2 to 10°C, 3 to 10°C, 4 to 10°C, and more preferably 5 to 10°C. In this specification, the glass transition temperature can be measured using a differential scanning calorimeter (DSC measuring device) in accordance with JIS-K7121-1987.
[0033] (Weight average molecular weight of acid-modified chlorinated polyolefin) The lower limit of the weight average molecular weight of the acid-modified chlorinated polyolefin is preferably 100,000 or more, more preferably 110,000 or more, and even more preferably 120,000 or more. This can improve the cohesive force of the resulting dispersion composition, and can exhibit adhesion to the substrate. The upper limit is preferably 150,000 or less, more preferably 140,000 or less, and even more preferably 130,000 or less. This can improve the compatibility of the resulting dispersion composition with other resins and the solubility in solvents. Therefore, the weight average molecular weight is preferably 100,000 to 150,000, more preferably 110,000 to 140,000, and even more preferably 120,000 to 130,000.
[0034] (Softening point of acid-modified chlorinated polyolefin) The softening point of the acid-modified chlorinated polyolefin is preferably 70°C or higher, more preferably 80°C or higher. This can suppress blocking when solidified. The upper limit is preferably 100°C or lower, more preferably 95°C or lower. This can show good low-temperature adhesion. In this specification, the softening point can be measured by the method in the examples.
[0035] Component A may be a single acid-modified chlorinated polyolefin, or a combination of two or more acid-modified chlorinated polyolefins having different structures, production methods, etc. In the case of a combination of two or more, the weight ratio of each is not particularly limited.
[0036] [1.2 Component B: Nonionic surfactant] Component B is a nonionic surfactant. By containing component B, the composition can function as an emulsifier and can increase the dispersibility of component A in component D (aqueous medium). In addition, the water resistance of the coating film can be improved, and the high-pressure car washability and warm water resistance can be further improved.
[0037] Examples of nonionic surfactants include polyoxyethylene alkyl ethers, polyoxyethylene alkylene alkyl ethers, polyoxyethylene derivatives, polyoxyethylene fatty acid esters, polyoxyethylene polyhydric alcohol fatty acid esters, polyoxyethylene propylene polyols, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene hydrogenated castor oil, polyoxyalkylene polycyclic phenyl ethers, polyoxyethylene alkylamines, alkyl alkanolamides, and polyalkylene glycol (meth)acrylates, of which polyoxyethylene alkyl ethers, polyoxyethylene fatty acid esters, polyoxyethylene sorbitan fatty acid esters, and polyoxyethylene alkylamines are preferred, and polyoxyethylene alkyl ethers and polyoxyethylene alkylamines are preferred.
[0038] Examples of polyoxyethylene alkyl ether nonionic surfactants include polyoxyethylene alkyl ethers having an alkyl group having 10 to 30, preferably 12 to 25, carbon atoms, such as polyoxyethylene myristyl ether, polyoxyethylene oleyl ether, polyoxyethylene cetyl ether, polyoxyethylene behenyl ether, and polyoxyethylene octyldodecyl ether, and preferably polyoxyethylene oleyl ether.
[0039] Component B may be a single nonionic surfactant or a combination of two or more nonionic surfactants. In the case of a combination of two or more nonionic surfactants, the weight ratio of each surfactant is not particularly limited.
[0040] The content of component B in the composition is usually 10% by weight or more, preferably 15% by weight or more, more preferably 20% by weight or more, based on 100% by weight of the content of component A. This can increase the solubility of component A, reduce the particle size contained in the composition, improve stability, and improve adhesion to the substrate and coating film properties. The upper limit is usually 30% by weight or less, preferably 25% by weight or less. This can suppress the plasticity of the coating film and the bleeding of the surfactant, and can suppress the occurrence of blocking of the coating film. The content of component B is usually the same as the amount of component C added when producing the composition.
[0041] [1.3 Component C: Basic compounds] Component C is a basic compound. By containing component C in the composition, the pH of the composition can be appropriately adjusted, and the dispersibility and storage stability of component A (acid-modified chlorinated polyolefin) in component D (aqueous medium) can be further improved.
[0042] Examples of basic compounds include sodium hydroxide, potassium hydroxide, ammonia, methylamine, propylamine, hexylamine, octylamine, ethanolamine, propanolamine, diethanolamine, N-methyldiethanolamine, dimethylamine, diethylamine, triethylamine, N,N-dimethylethanolamine, 2-dimethylamino-2-methyl-1-propanol, 2-amino-2-methyl-1-propanol, morpholine, dimethylethanolamine, and 2-amino-2-ethyl-1,3-propanediol. Preferred are primary amines such as methylamine, propylamine, hexylamine, octylamine, ethanolamine, propanolamine, 2-amino-2-methyl-1-propanol (AMP), and 2-amino-2-ethyl-1,3-propanediol, with AMP being preferred.
[0043] Component C may be a single basic compound or a combination of two or more basic compounds. In the case of a combination of two or more basic compounds, the weight ratio of each basic compound is not particularly limited.
[0044] The content of component C in the composition is not particularly specified, but is usually 1.0% by weight or more, preferably 2.0% by weight or more, and more preferably 3.0% by weight or more, based on 100% by weight of the content of component A. This allows the pH of the composition to be kept within an appropriate range. The upper limit is preferably 3.0 times the equivalent amount of the carboxyl group in the acid-modified chlorinated polyolefin, which is component A. The content of component C is usually the same as the amount of component C added when producing the composition.
[0045] The pH of the composition is preferably 5 or more, more preferably 6 or more. This can improve the dispersibility of component A in component D, suppress the occurrence of precipitation and separation, and maintain storage stability. The upper limit is usually 11 or less. This can appropriately maintain the compatibility of component C with other components and operational safety. Therefore, the pH of the composition is preferably 5 or more, more preferably 6 to 11. The content of component C is preferably an amount such that the pH of the composition is in the above range.
[0046] [1.4 Component D: Aqueous medium] Component D is an aqueous medium. The aqueous medium is a dispersion medium for the composition. Examples of the aqueous medium include water and a hydrophilic substance. Examples of the hydrophilic substance include alcohol-based, ketone-based, and ester-based hydrophilic substances, and methanol, ethanol, isopropyl alcohol, and acetone are preferred.
[0047] Component D may be one aqueous medium alone or a combination of two or more, and preferably contains at least water. In the case of a combination of two or more, the weight ratio of each is not particularly limited.
[0048] The content of component D in the composition can be expressed by the solid content of the composition. The solid content of the composition is preferably 1% by weight or more, more preferably 5% by weight or more, even more preferably 10% by weight or more, and even more preferably 15% by weight or more. The upper limit is preferably 70% by weight or less, more preferably 60% by weight or less, even more preferably 50% by weight or less, and even more preferably 40% by weight or less. Therefore, it is preferably 5% by weight to 60% by weight, more preferably 10% by weight to 50% by weight, and even more preferably 15% by weight to 40% by weight. This can improve the stability over time.
[0049] [1.5 Component E: Glycol ether compounds] Component E is a glycol ether compound. By including Component E in the composition, it is possible for it to function as an emulsifying aid, promote the emulsifying action of Component B, and improve the stability of the composition and the coating performance.
[0050] The molecular weight of the glycol ether compound is usually less than 200, preferably 190 or less, 180 or less, 170 or less, 160 or less, or 150 or less. This allows the compound to better function as an emulsifier. In this specification, the molecular weight of the glycol ether compound is the molecular weight determined from the relative atomic mass (12C=12) approved by the IUPAC Atomic Weights Commission.
[0051] The glycol ether compound is usually a compound having a structure in which a hydrogen atom in one hydroxyl group of glycols such as ethylene glycol, propylene glycol, butylene glycol, etc. is substituted with an alkyl group. For example, a compound represented by the following general formula (I) is preferred. The compound represented by the general formula (I) has a hydrophobic group and a hydrophilic group in one molecule, so that it can further increase the dispersibility of component A and contribute to the storage stability of the composition. C a H 2a+1 -O-(C b H 2b O) c H···(I) In the general formula (I), a to c are each independently an integer. a is usually an integer of 10 or less, preferably 8 or less, 7 or less, 6 or less, 5 or less, or 4 or less. The lower limit of a is not particularly limited, but is, for example, 1 or more. b is usually 5 or less, 4 or less, or 3 or less. The lower limit of b is not particularly limited, but is, for example, 2 or more. c is usually 5 or less, preferably 4 or less, 3 or less, or 2 or less. The lower limit of c is not particularly limited, but is, for example, 1 or more.
[0052] Examples of the compound represented by the general formula (I) include ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether (butyl cellosolve), ethylene glycol monoisobutyl ether, ethylene glycol mono-t-butyl ether, ethylene glycol monohexyl ether, ethylene glycol monodecyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, etc. Among these, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether (butyl cellosolve), ethylene glycol mono-t-butyl ether, propylene glycol monomethyl ether, and propylene glycol monopropyl ether are preferred, and ethylene glycol monobutyl ether (butyl cellosolve) is more preferred.
[0053] Component E may be one glycol ether compound alone or a combination of two or more. In the case of a combination of two or more, the weight ratio of each is not particularly limited.
[0054] The content of component E in the composition is usually 2.0% by weight or less. There is no particular lower limit.
[0055] [1.6 Other ingredients] The composition may contain, as necessary, components other than the above-mentioned components A to E. Examples of such components include stabilizers, crosslinking agents, diluents, curing agents, resin components other than component A, emulsifiers other than component B, other additive components (e.g., lower alcohols, lower ketones, lower esters, preservatives, leveling agents, antioxidants, light stabilizers, ultraviolet absorbers, dyes, pigments, metal salts, acids), and unreacted raw materials (e.g., α,β-unsaturated carboxylic acids or derivatives thereof, polyolefins, and chlorine).
[0056] (Stabilizer) Examples of the stabilizer include epoxy stabilizers (compounds containing an epoxy group). Examples of the epoxy stabilizer include epoxy compounds having an epoxy equivalent of about 100 to 500 and containing one or more epoxy groups in one molecule. More specifically, examples of the epoxy compounds include epoxidized soybean oil and linseed oil obtained by epoxidizing vegetable oils having natural unsaturated groups with peracids such as peracetic acid; epoxidized fatty acid esters obtained by epoxidizing unsaturated fatty acids such as oleic acid, tall oil fatty acid, and soybean oil fatty acid; epoxidized alicyclic compounds such as epoxidized tetrahydrophthalate; monoepoxy compounds such as bisphenol A glycidyl ether, ethylene glycol glycidyl ether, propylene glycol glycidyl ether, glycerol polyglycidyl ether, and sorbitol polyglycidyl ether, which are obtained by condensing bisphenol A or polyhydric alcohol with epichlorohydrin; and monoepoxy compounds such as butyl glycidyl ether, 2-ethylhexyl glycidyl ether, decyl glycidyl ether, stearyl glycidyl ether, allyl glycidyl ether, phenyl glycidyl ether, sec-butylphenyl glycidyl ether, tert-butylphenyl glycidyl ether, and phenol polyethylene oxide glycidyl ether.
[0057] The stabilizer may be a compound that does not contain an epoxy group, and examples thereof include metal soaps such as calcium stearate and lead stearate; organometallic compounds such as dibutyltin dilaurate and dibutyl malate; hydrotalcite compounds; and oxetane compounds.
[0058] (Other resin components) Examples of resin components other than component A include urethane resin, epoxy resin, acrylic resin, phenol resin, alkyd resin, polyamide resin, polyimide resin, silicone resin, nitrocellulose, and combinations of two or more of these. These resins may be blended into the composition as water-based products (e.g., water-based acrylic resin, water-based polyurethane resin). The ratio of the content of component A to the other resin components (total amount when the other resins are two or more) is, in terms of solid matter, component A:other resin components=1 to 99:99 to 1, preferably 10 to 90:90 to 10, more preferably 20 to 80:80 to 20, and even more preferably 30 to 70:70 to 30.
[0059] Examples of the crosslinking agent include blocked isocyanate compounds, aliphatic or aromatic epoxy compounds, amine compounds, and amino resins. The addition of the crosslinking agent reacts with groups such as hydroxyl groups, carboxy groups, and amino groups contained in the components constituting the composition such as components A to C to form a crosslinked structure.
[0060] [1.7 Physical properties of the composition] The composition has the form of a dispersion in which solid contents of components A to C and the like are dispersed in component D. (Average particle size) In the composition, solid components such as component A are usually present as particles dispersed in component D. The average particle size of the particles is preferably 300 nm or less, more preferably 200 nm or less. If it is 300 nm or less, the storage stability and compatibility of the composition can be maintained, but if it exceeds 300 nm, the adhesion to the substrate and the coating film properties may be reduced. The average particle size can be adjusted by the content and type of each component in the composition and the dispersion conditions (e.g., stirring force, stirring time) when preparing the composition. The average particle size can be obtained by particle size distribution measurement using a light diffusion method.
[0061] [2. Method for producing the composition] The method for producing the composition is not particularly limited. For example, a method including at least a dispersion step of adding and mixing components A to D and dispersing component A in component D can be mentioned. Each component may be added all at once or successively, but it is preferable to add components A and B to the system, add component C, and then add component D last. According to one embodiment, a method can be mentioned in which components A and B are dissolved (preferably under heating conditions) in an organic solvent (e.g., an aromatic hydrocarbon solvent such as toluene, o-xylene, m-xylene, p-xylene, ethylbenzene, etc.) together with a stabilizer as necessary, and then component C is added, and then component D (preferably warm water) is added. The added organic solvent can be distilled off after the addition of component D. When the composition contains another resin component, it is preferable to mix the resin component after the dispersion step. For example, after the dispersion step, a resin component mixing step may be performed in which a resin component is mixed and the solid content is adjusted as necessary (e.g., by adding a dispersion medium to dilute).
[0062] [3. Use of the composition] The composition has good adhesion to substrates that are difficult to coat with paints, such as non-polar plastic substrates (e.g., polyolefin substrates such as polypropylene and ABS substrates), and can form coating films that are highly resistant to hot water. Therefore, the composition can be used as paints, inks, adhesives, and binders for these, and is particularly useful as a coating material for automobiles (e.g., paints and binders). EXAMPLES
[0063] The present invention will be described in detail below with reference to examples. The following examples are provided to better explain the present invention, but are not intended to limit the present invention. The methods for measuring physical properties are as described below unless otherwise specified. In addition, unless otherwise specified, parts and % refer to parts by weight and % by weight, and the numerical ranges are described as including their endpoints.
[0064] [Physical property measurement method]: The graft amount of acid component, the degree of chlorination (graft amount of chlorine), the glass transition temperature, the weight average molecular weight (Mw), and the softening point were measured using acid-modified chlorinated polyolefin. The details of the measurement method are shown below.
[0065] (Acid modification degree (wt%)) Measurements were carried out using the alkali titration method in accordance with JIS-K0070:1992, and calculations were made.
[0066] (Chlorination degree (wt%)) The measurements were carried out according to JIS-K7229:1995.
[0067] (Glass transition temperature (℃)) About 5 g of the sample sealed in an AL pan (manufactured by TA Instruments) was placed in a DSC measuring device (TA Instruments, DISCOVERY DSC2500), cooled to -50°C at -10°C / min, and held for 5 minutes. The temperature was then raised to 150°C at 10°C / min, and held for 5 minutes. This cooling and heating cycle was repeated twice to obtain a DSC curve. Next, in accordance with JIS-K7121-1987, an extension line (line 1) was drawn on the low-temperature side of the baseline of the DSC curve, and an extension line (line 2) was drawn on the high-temperature side of the baseline. A line (line 3) was also drawn in the middle of lines 1 and 2, parallel to the two lines. The temperature at the intersection of the step-like change curve of the glass transition and line 3 was taken as the glass transition temperature (°C) of the sample.
[0068] (Weight average molecular weight (Mw)) The resins produced in the Production Examples were measured by GPC under the following conditions. Equipment: HLC-8320GPC (Tosoh Corporation) Column: TSK-gel G-6000HXL, G-5000HXL, G-4000HXL, G-3000HXL, G-2000HXL (manufactured by Tosoh Corporation) Eluent: Tetrahydrofuran Flow rate: 1mL / min Temperature: Pump oven, column oven 40℃ Injection volume: 100μL Standard material: Polystyrene EasiCal PS-1 (Agilent Technology, Inc.)
[0069] [Softening point (℃)] A piece of resin sample dried at 40°C was heated at 3.5°C per minute on a temperature-controlled stage, and the change in shape of the sample (melted state) was observed under a microscope. The temperature at which the sample began to melt and was completely melted was evaluated as the softening point temperature.
[0070] [Tm (melting point, °C)]: In accordance with JIS K7121-1987, a DSC measuring device (manufactured by TA Instruments) was used to heat and melt approximately 5 mg of the sample at 150° C. for 10 minutes. The temperature was then lowered at a rate of 10° C. / min and the sample was stably held at −50° C. The temperature was then raised to 150° C. at a rate of 10° C. / min, and the melting peak temperature at which the sample melted was taken as Tm.
[0071] [Production Example 1: Acid-modified chlorinated propylene-ethylene copolymer a] (1) Maleinization 100 parts of polyolefin resin (propylene-ethylene copolymer, propylene unit 97.0 mol%, ethylene unit 3.0 mol%, Tm = 125 ° C., weight average molecular weight 315,000) with a melt mass flow rate of 0.24 g / min (measured according to JIS K7210-1), 2.5 parts of maleic anhydride, and 0.5 parts of di-tert-butyl peroxide were premixed in a stirrer and heated and kneaded at 175 ° C. in a same-rotation twin-screw extruder to obtain an acid-modified propylene-ethylene copolymer. The graft weight of maleic anhydride of the obtained acid-modified propylene-ethylene copolymer was 1.2 wt%, and Tm was 122 ° C. (Table 1).
[0072] (2) Chlorination 1,200 kg of the acid-modified propylene-ethylene copolymer obtained by the above-mentioned maleinization reaction was put into a glass-lined reaction vessel, 8,700 L of chloroform was added, and the mixture was thoroughly dissolved at a temperature of 115°C under a pressure of 0.4 MPa. Then, 1,160 g of radical reaction initiator tert-butyl peroxy octoate was added, and the chlorination reaction was carried out by blowing gaseous chlorine into the reaction vessel while controlling the pressure inside the vessel to 0.4 MPa, to obtain a reaction liquid containing a chlorinated acid-modified propylene-ethylene copolymer with a chlorination degree of 20.0%. Next, an epoxy compound was added as a stabilizer, and chloroform was removed using a vented twin-screw extruder equipped with a vent port for distilling off the reaction solvent under reduced pressure. The resulting composition was extruded into a strand shape and cooled with water. Then, the mixture was pelletized using a water-cooled pelletizer to obtain an acid-modified chlorinated propylene-ethylene copolymer a (solid matter). The obtained copolymer a was analyzed by gel permeation chromatography (GPC; HLC8320GPC, manufactured by Tosoh Corporation) and found to have a weight average molecular weight (Mw) of 130,000, a glass transition temperature of 5°C, and a softening point of 80 to 95°C (Table 1).
[0073] [Production Example 2: Production of Acid-Modified Chlorinated Propylene-Ethylene Copolymer b] A reaction liquid containing a chlorinated acid-modified propylene-ethylene copolymer (component A) with a chlorination degree of 22.0% by weight was obtained in the same manner as in Production Example 1, except that the chlorine blowing time (blowing amount) was extended from that in Production Example 1. Next, an epoxy compound was added as a stabilizer, chloroform was removed using a vented twin-screw extruder equipped with a vent port for distilling off the reaction solvent under reduced pressure, and the resulting composition was extruded into a strand shape and cooled with water. Then, it was pelletized using a water-cooled pelletizer to obtain an acid-modified chlorinated propylene-ethylene copolymer b (solid matter). The obtained copolymer b was analyzed by gel permeation chromatography (GPC; HLC8320GPC, manufactured by Tosoh Corporation), and as a result, the weight average molecular weight (Mw) was 130,000, the glass transition temperature was 10°C, and the softening point was 70 to 85°C.
[0074] [Production Example 3: Production of Acid-Modified Chlorinated Propylene-Ethylene Copolymer c] A reaction liquid containing a chlorinated acid-modified propylene-ethylene copolymer (component A) with a chlorination degree of 15.5% by weight was obtained in the same manner as in Production Example 1, except that the chlorine blowing time (blowing amount) was shortened from that in Production Example 1. Next, an epoxy compound was added as a stabilizer, chloroform was removed using a vented twin-screw extruder equipped with a vent port for distilling off the reaction solvent under reduced pressure, and the resulting composition was extruded into a strand shape and cooled with water. Then, it was pelletized using a water-cooled pelletizer to obtain an acid-modified chlorinated propylene-ethylene copolymer c (solid matter). The obtained copolymer c was analyzed by gel permeation chromatography (GPC; HLC8320GPC, manufactured by Tosoh Corporation), and the weight average molecular weight (Mw) was 130,000, the glass transition temperature was 0°C, and the softening point was 90 to 100°C (Table 1).
[0075] [Production Example 4: Production of Acid-Modified Chlorinated Propylene-Ethylene Copolymer d] (1) Maleinization 100 parts of polyolefin resin (propylene-ethylene copolymer, propylene unit 97.0 mol%, ethylene unit 3.0 mol%, Tm = 125 ° C., weight average molecular weight 315,000) with a melt mass flow rate of 0.24 g / min (measured according to JIS K7210-1), 4.0 parts of maleic anhydride, and 3.0 parts of di-tert-butyl peroxide were premixed with a stirrer and heated and kneaded at 200 to 210 ° C. in a same-rotation twin-screw extruder to obtain an acid-modified propylene-ethylene copolymer. The graft weight of maleic anhydride of the obtained acid-modified propylene-ethylene copolymer was 2.5 wt%, and Tm was 122 ° C. (Table 1). (2) Chlorination 1,350 kg of the acid-modified propylene-ethylene copolymer obtained by the above-mentioned maleinization reaction was put into a glass-lined reaction vessel, 9,000 L of chloroform was added, and the mixture was thoroughly dissolved at a temperature of 115°C under a pressure of 0.4 MPa. Then, 1,310 g of the radical reaction initiator tert-butyl peroxy octoate was added, and the chlorination reaction was carried out by blowing gaseous chlorine into the reaction vessel while controlling the pressure inside the vessel to 0.4 MPa, thereby obtaining a reaction liquid containing a chlorinated acid-modified propylene-ethylene copolymer with a chlorination degree of 25.0%. Next, the evaporator was distilled under reduced pressure to concentrate the reaction liquid, and an epoxy compound was added as a stabilizer. Then, the concentrated liquid was distilled under reduced pressure while adding toluene, and the solvent replacement was stopped after the recovered solvent reached a predetermined specific gravity. Toluene, cyclohexane, and 1-butanol were added to the obtained replacement liquid to adjust the solvent composition to the specified value (toluene / cyclohexane / 1-butanol = 89·9 / 10 / 0.1), and acid-modified chlorinated propylene-ethylene copolymer c (20.0% solution) was obtained. Copolymer c was analyzed by gel permeation chromatography (GPC; HLC8320GPC, Tosoh Corporation), and the weight average molecular weight (Mw) was 80,000, the glass transition temperature was 15°C, and the softening point was 65-75°C (Table 1).
[0076] [Table 1]
[0077] [Example 1] In a 3L scale four-neck flask equipped with a stirrer, a cooling tube, and a dropping funnel, 200 g of component A: acid-modified chlorinated propylene-ethylene copolymer a obtained in Production Example 1, 42 g of component B: nonionic surfactant (polyoxyethylene oleyl ether), 7 g of stabilizer Denacol EX-146 (para-tert-butylphenyl glycidyl ether, Nagase ChemteX Corporation) (3.5 parts by weight relative to 100 parts by weight of component A), and 150 g of toluene were added and kneaded at 100 ° C for 40 minutes. Next, 3.4 g of component C: basic compound 2-amino-2-methyl-1-propanol 90% aqueous solution (AMP-90, Dow Chemical Co., Ltd.) was added and held for 30 minutes, and then 90 ° C. component D: hot water was added over about 2 hours. After that, a reduced pressure treatment was performed to remove the toluene, and the mixture was cooled to room temperature while stirring to obtain an aqueous dispersion 1 of acid-modified chlorinated propylene-ethylene copolymer a.
[0078] [Example 2] The same operation as in Example 1 was carried out, except that in addition to Components A to C used in the emulsification step, 16 g of Component E (butyl cellosolve) was added together with toluene, to obtain an aqueous dispersion 2 of acid-modified chlorinated propylene-ethylene copolymer a.
[0079] [Example 3] The component B used in the emulsification step was changed to 20 g of a nonionic surfactant (polyoxyethylene alkyl ether), 5.6 g of component C, 100 g of toluene, and 100 g of component E. After the addition of component D, a cooling treatment was performed to 40° C. The rest of the procedure was the same as in Example 1, and an aqueous dispersion 3 of an acid-modified chlorinated propylene-ethylene copolymer a of Example 3 was obtained.
[0080] [Example 4] The component B used in the emulsification step was changed to 42 g of a nonionic surfactant (polyoxyethylene oleylamine), 5.6 g of component C, 120 g of toluene, and 30 g of component E. In addition, component B was added at 80° C. after adding component C and holding for 30 minutes. The rest of the procedure was the same as in Example 1, and an aqueous dispersion 4 of an acid-modified chlorinated propylene-ethylene copolymer a of Example 4 was obtained.
[0081] [Example 5] The component B used in the emulsification step was changed to 30 g of a nonionic surfactant (polyoxyethylene oleylamine), 5.6 g of component C, 120 g of toluene, and 70 g of component E. Component B was added at 80°C after adding component C and holding for 30 minutes. After adding component D, a cooling treatment was performed to 40°C. The rest of the procedure was the same as in Example 1, and an aqueous dispersion 5 of an acid-modified chlorinated propylene-ethylene copolymer a of Example 5 was obtained.
[0082] [Example 6] Component A used in the emulsification step was changed to the acid-modified chlorinated propylene-ethylene copolymer b obtained in Production Example 2, and further changed to 5.6 g of component C, 120 g of toluene, and 70 g of component E. After adding component D, a cooling treatment was performed to 40° C. The rest of the procedure was the same as in Example 1, and an aqueous dispersion 6 of the acid-modified chlorinated propylene-ethylene copolymer b of Example 6 was obtained.
[0083] [Comparative Example 1] Except for changing the component A used in the emulsification step to the acid-modified chlorinated propylene-ethylene copolymer c obtained in Production Example 3, the same operation as in Example 1 was performed to obtain an aqueous dispersion 7 of the acid-modified chlorinated propylene-ethylene copolymer c.
[0084] [Comparative Example 2] The component A used in the emulsification step was changed to 600 g of acid-modified chlorinated propylene-ethylene copolymer d (20.0% solution), and the mixture was subjected to a reduced pressure treatment at a temperature of 100°C to remove solvents such as toluene. Then, 25.2 g of component B: nonionic surfactant (polyoxyethylene oleyl ether), 4.2 g of stabilizer Denacol EX-146 (3.5 parts by weight relative to 100 parts by weight of component A), 72 g of toluene, and 24 g of component E were added and kneaded at 100°C for 40 minutes. Next, 4.8 g of component C was added and held for 30 minutes, after which component D at 90°C was added over about 2 hours. Then, the mixture was subjected to a reduced pressure treatment to remove toluene and component E, and then cooled to room temperature while stirring to obtain an aqueous dispersion 8 of acid-modified chlorinated propylene-ethylene copolymer d.
[0085] The following tests were carried out using the aqueous dispersions 1 to 8 obtained in Examples 1 to 6 and Comparative Examples 1 and 2. The results are shown in Table 2.
[0086] In order to easily evaluate high-pressure car washability, a cross-cut peel test was conducted in which diagonal cuts were made immediately after heating (hereinafter referred to as the diagonal cross-cut peel test), which is a more severe test than the usual cross-cut peel test.
[0087] [Diagonal checkerboard peeling test (high pressure car washability) evaluation] (Preparation of test panels) The surface of the ultra-high rigidity polypropylene plate was degreased with isopropyl alcohol, and the aqueous dispersion compositions obtained in Examples 1 to 6 and Comparative Examples 1 and 2 were applied to the plate by an air-type spray gun so that the dry film thickness was about 10±3 μm, and the plate was preheated at 80° C. for 3 minutes. Next, a solvent-based base coat paint was applied to the plate so that the dry film thickness was about 20 μm, and the plate was left at room temperature for about 10 minutes. After that, an acrylic urethane solvent-based clear paint was applied to the plate so that the dry film thickness was about 25 to 30 μm, and the plate was left at room temperature for about 10 minutes. Then, the plate was baked at 100° C. for 30 minutes and left at room temperature for 72 hours to prepare a test plate.
[0088] The test plate was immersed in 60°C water for 30 minutes, and then removed. Immediately afterwards, 25 checkerboard-shaped cuts were made at 2mm intervals with a cutter knife at a 45° angle into the coating film, reaching the surface of the coating film, and cellophane adhesive tape was adhered onto the cuts and peeled off 10 times at 180°. The peeling state of the coating film was evaluated according to the following criteria: [◎], [◯], [△], and [×]. ◎: No peeling on any grid ○: There is slight peeling at the cut area. △: There is slight peeling at the cut area and the corners are chipped. ×: Peeling occurred in the grid.
[0089] [Evaluation of hot water resistance test] (Preparation of test panels) The surface of the ultra-high rigidity polypropylene plate was degreased with isopropyl alcohol, and a mixture of the aqueous dispersion composition obtained in Examples 1 to 6 and Comparative Examples 1 and 2 and a urethane emulsion (UWS-145, manufactured by Sanyo Kasei Co., Ltd.) in a mixing ratio (weight%) of 1:1 was applied to the plate using an air-type spray gun so that the dry film thickness was about 10±3 μm, and preheated at 80° C. for 3 minutes. Next, a solvent-based base coat paint was applied to the plate so that the dry film thickness was about 20 μm, and the plate was left at room temperature for about 10 minutes, after which an acrylic urethane solvent-based clear paint was applied to the plate so that the dry film thickness was about 25 to 30 μm, and the plate was left at room temperature for about 10 minutes. Then, the plate was baked at 100° C. for 30 minutes and left at room temperature for 72 hours to prepare a test plate.
[0090] The test plate thus prepared was immersed in hot water at 60°C for 10 days, and then immersed in water at 23°C for 1 hour, after which the swelling (blistering) of the coating was visually observed. Then, 100 cuts were made in a grid pattern on the coating film at 2mm intervals with a cutter knife, reaching down to the substrate, and cellophane adhesive tape was applied on top of the cuts, which were then peeled off 10 times at an angle of 180 degrees, and the adhesion in the hot water resistance test was evaluated according to the following criteria: [◎], [◯], [△], and [×]. ◎: 100-90 remaining squares 〇: 89 to 80 remaining squares △: 79 to 60 remaining squares ×: 59 or less squares remaining
[0091] The blisters were evaluated based on the following criteria. Diameter: (large) 1 to 10 (small) Frequency: None, (few) F, M, MD, D (many) The diameter is the size of the blister, and the maximum value that can be visually confirmed is 8. The frequency is the number of blisters, and is an abbreviation for F (Few), M (Medium), MD (Medium Dense), and D (Dense). For example, "4M" indicates a blister diameter of 4 and a blister frequency of M.
[0092] [Table 2]
[0093] With respect to the evaluation of the diagonal checkerboard peeling test, the results of Examples 1 to 6 tend to show equal or better adhesion than Comparative Examples 1 and 2, and it is understood that Examples 2, 4, and 5 show excellent adhesion. With respect to the evaluation of the hot water resistance test, it is understood that although blisters were generated in all except Example 2, the degree of the blisters was less in Examples 1, 3, and 6 than in Comparative Examples 1 and 2. Furthermore, all of Examples 1 to 6 showed superior adhesion to Comparative Examples 1 and 2. Judging these results comprehensively, the composition of the present invention shows excellent adhesion and can form a coating film having high-pressure car washability and hot water resistance.
Claims
1. Component A: an acid-modified chlorinated polyolefin having a degree of chlorination of 17 to 23% by weight and a glass transition temperature of 0 to 10° C.; Component B: nonionic surfactant, Component C: a basic compound, and Component D: Aqueous medium Including, The content of component B is 10% by weight or more when the content of component A is 100% by weight, The weight average molecular weight of component A is 100,000 to 150,000; A dispersion composition, wherein component B is a polyoxyethylene alkyl ether-based nonionic surfactant.
2. 2. The dispersion composition according to claim 1, wherein the acid-modified chlorinated polyolefin has a softening point of 70 to 100°C.
3. The dispersion composition of claim 1 or 2, wherein component C comprises a primary amine.
4. Component E: The dispersion composition according to claim 1 or 2, further comprising a glycol ether-based compound having a molecular weight of less than 200.
5. 3. The dispersion composition of claim 1 or 2 which is a paint or a binder for a paint.
Citation Information
Patent Citations
Aqueous dispersion, its manufacturing method and use
JP2003327761A
Aqueous wax agent for car washing
JP2005263934A
Modified polyolefin resin, aqueous dispersion, and primer
JP2020026487A
Polyolefin resin dispersion composition and process for producing the same
WO2008072689A1
Chlorinated polyolefin resin composition
WO2013146728A1